How Social Information Networks Reflect Major Life Events: Case of Childbirth - Choudhury, Munmun De; Counts, Scott; Horvitz, Eric (Proceedings of the 16th ACM Conference on Computer Supported Cooperative Work (San Antonio, TX, USA, Feb 23-27, 2013). CSCW 2013., 2013)
Social information networks, such as Twitter and Facebook provide powerful tools for individuals to share thoughts, opinions, and emotions as well as to create and maintain social ties. Considerable research in the recent past has focused on the understanding of large-scale social processes enabled by the availability of data derived from content and activity on social networks, spanning multiple domains including finance, politics, epidemiology and public health, marketing, and crisis mitigation. Beyond exploration and inferences about population-scale dynamics and phenomena, social information networks can also provide insights at an individual scale about evolution and changes of intentions, language, mood, and behavior. As increasingly large numbers of people have been using social information networks over time scales measured in years, these networks can serve as windows onto a variety of important developments in an individual’s personal life, including such events as childbirth, death of a loved one, marriage, divorce, loss of a job, and traumatic experiences such as an accident or a disaster event. From a research perspective, this allows for nuanced individual-level behavioral analyses in a longitudinal manner; over time scales long enough to include periods before and after one or more major life events. In this light, we explore the harnessing of social information networks as a lens on behavioral changes of individuals around a particular major life event: childbirth. Having a baby is a major life event that creates significant changes in the lives of new mothers. Sleep and daily routines are disrupted, and adjustments must be made in personal and professional lives.
Best Paper Nomination